Studies on the Physiological Chemistry of the Tibio-Tarsal Synovial Fluid of Healthy Bovines - Amrousi, S. El. (1966)
The physical properties, chemical composition and cytological content of the synovial fluid of healthy native breed cattle, obtained by tibio-tarsal arthrocentesis, was studied. Normally the synovial fluid of bovines is a clear, colourless or straw coloured, viscous, non-coagulable liquid with a normal mucin precipitate quality. The fluid is alkaline in reaction and with a lower specific gravity than serum. Bovine tibio-tarsal fluid exhibits no erythrocytes and presents a low leucocytic count which is dominated by lymphocytes and monocytes. Compared to bovine serum, synovial fluid contains almost the same levels of sugar, urea, creatinine and phosphorous; slightly lower calcium concentration and rather higher chlorides. The fluid is devoid of any traces of bilirubin. Young calves showed a significantly lower total leucocyte number, chloride level and sugar content and a higher calcium and inorganic phosphorous than bulls.